ThresholdFP: Enhanced Durability in Browser Fingerprinting - Elif Ecem Samlioglu; Sinan Emre Tasci; Muhammed Fatih Gulsen; Albert Levi (IEEE Access)
Browser fingerprinting is a powerful tool for user identification in financial and other security-critical applications that require strong authentication. However, due to the instability of browser attributes, fingerprints often change rapidly, reducing their lifespan and negatively impacting user convenience. We propose, a novel linking algorithm designed to extend the durability of browser fingerprints without compromising precision. Instead of replacing the fingerprint after even a small change, computes a difference score between fingerprints and tolerates variations as long as they stay within a predefined threshold. To ensure realistic performance evaluation, we collected and utilized two real-world datasets. Comparative results show that the fingerprints generated by are significantly more persistent than those produced by existing methods, while maintaining near-perfect precision. Notably, our approach achieves an improvement in average tracking duration ranging from 24.33% to 106.30% compared to rival schemes in the literature.